2017
DOI: 10.1002/pds.4320
|View full text |Cite
|
Sign up to set email alerts
|

A 15‐year overview of increasing tramadol utilisation and associated mortality and the impact of tramadol classification in the United Kingdom

Abstract: Increasing tramadol utilisation was influenced by the increase in prevalence and incidence of tramadol users, mean daily dose, and day of supply. Prevalence of tramadol users, tramadol utilisation, and reported deaths declined after tramadol classification. Future studies need to evaluate the influencing factors to ensure the safety of long-term tramadol use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 28 publications
2
25
0
1
Order By: Relevance
“…10 Furthermore, data on 11.3 million patients from the Clinical Practice Research Datalink showed that the tramadol-related death rate increased before tramadol was classified as a Schedule III controlled substance in 2014 in the United Kingdom, and decreased thereafter. 13 However, a small study of 272 patients who underwent hip replacement due to fracture showed that tramadol prescription was not associated with increased mortality within 6 months after surgery compared with no prescription of tramadol. 11 Another study failed to show a statistically significant mortality difference between prescription of tramadol alone or in combination with codeine compared with infrequent or no prescription of tramadol alone or combined with codeine among 8866 patients with Crohn disease and ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, data on 11.3 million patients from the Clinical Practice Research Datalink showed that the tramadol-related death rate increased before tramadol was classified as a Schedule III controlled substance in 2014 in the United Kingdom, and decreased thereafter. 13 However, a small study of 272 patients who underwent hip replacement due to fracture showed that tramadol prescription was not associated with increased mortality within 6 months after surgery compared with no prescription of tramadol. 11 Another study failed to show a statistically significant mortality difference between prescription of tramadol alone or in combination with codeine compared with infrequent or no prescription of tramadol alone or combined with codeine among 8866 patients with Crohn disease and ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Liner regression was used to perform a trend analysis overtime to obtain the average annual changes in utilisation overtime. The correlation (strength of association) between the opioids and gabapentinoids utilisation and related mortality trends was assessed using Pearson coefficient ( Sedgwick, 2012 ) and presented as a correlation coefficient (range from 1- to 1) as a mean of hypothesis generation; similar approach has been used in other studies using ecological, aggregated dataset ( Ganmaa et al, 2002 ) We did not include in the analysis the time points where the various relevant opioids and gabapentinoids related-polices were introduced in the United Kingdom because assessing the impact of these policies was not the focus of our current study; besides, the impact of some of these policies such as the re-classification of tramadol ( Advisory Council on the Misuse of Drugs, 2013 ) has already been assessed and published in a previous study ( Chen et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Within the UK, the use of the weak opioid tramadol has increased over the past two decades [ 65 ]. In keeping with codeine, studies have demonstrated a probable reduced efficacy with tramadol in CYP2D6 PMs patients and, additionally, a lower risk of ADRs [ 66 ].…”
Section: Opioid Analgesicsmentioning
confidence: 99%